Ministerial decree no. 195/2017 on amending some provisions of the executive regulations of the income tax law promulgated by minister of finance decree no. 991/2005 = قرار وزاري رقم 195 لسنة 2017 بتعديل بعض أحكام اللائحة التنفيذية لقانون الضريبة على الدخل الصادر بقرار وزير المالية رقم 991 لسنة 2005 - Egypt. Ministry of trade and industry. The Egyptian Customs Authority (2025)
Ministry of finance decree no. 195 of the year 2017 amending provisions of the executive regulations of the income tax law promulgated by minister of finance decree no. 991 of the year 2005 وزارة المالية قرار رقم 195 لسنة 2017 بتعديل بعض أحكام اللائحة التنفيذية لقانون الضريبة على الدخل الصادر بقرار وزير المالية رقم 991 لسنة 2005